Mister Exam

Other calculators


n^(n-1)/factorial(n+1)

Sum of series n^(n-1)/factorial(n+1)



=

The solution

You have entered [src]
  oo          
____          
\   `         
 \      n - 1 
  \    n      
  /   --------
 /    (n + 1)!
/___,         
n = 1         
$$\sum_{n=1}^{\infty} \frac{n^{n - 1}}{\left(n + 1\right)!}$$
Sum(n^(n - 1)/factorial(n + 1), (n, 1, oo))
The radius of convergence of the power series
Given number:
$$\frac{n^{n - 1}}{\left(n + 1\right)!}$$
It is a series of species
$$a_{n} \left(c x - x_{0}\right)^{d n}$$
- power series.
The radius of convergence of a power series can be calculated by the formula:
$$R^{d} = \frac{x_{0} + \lim_{n \to \infty} \left|{\frac{a_{n}}{a_{n + 1}}}\right|}{c}$$
In this case
$$a_{n} = \frac{n^{n - 1}}{\left(n + 1\right)!}$$
and
$$x_{0} = 0$$
,
$$d = 0$$
,
$$c = 1$$
then
$$1 = \lim_{n \to \infty}\left(n^{n - 1} \left(n + 1\right)^{- n} \left|{\frac{\left(n + 2\right)!}{\left(n + 1\right)!}}\right|\right)$$
Let's take the limit
we find
False

False

False
The rate of convergence of the power series
The graph
Sum of series n^(n-1)/factorial(n+1)
    To see a detailed solution - share to all your student friends
    To see a detailed solution,
    share to all your student friends: